Highly Water-Absorptive and Antibacterial Hydrogel Dressings for Rapid Postoperative Detumescence - Fang, Yuan; Li, Haibo; Chen, Jingting; Xiong, Yao; Li, Xu; Zhou, Jianda; Li, Shengli; Wang, Shoubao; Sun, Binbin (Frontiers in Bioengineering and Biotechnology, 2022)
Postoperative wound edema, infection and pain burden the patient's life. Therefore, the purpose of this study is to develop an effective antibacterial, multifunctional application to prevent postoperative edema and relieve postoperative pain. To make full use of the dehydrating and analgesic effects of magnesium sulfate (MgSO4), magnesium oxide (MgO), sodium alginate (SA) and sodium carboxymethyl cellulose (Na-CMC) to make a composite hydrogel, which can promote postoperative detumescence. MgSO4//MgO/SA/Na-CMC composite hydrogel dressing shows outstanding mechanical properties, highly water absorption, and good biocompatibility. MgSO4 endows the hydrogel dressing with excellent antibacterial properties and better antibacterial activity against common bacteria and multi-drug resistant bacteria. In addition, MgSO4//MgO/SA/Na-CMC hydrogel dressing shows superior dehydration and analgesic properties in the postoperative nude mice model. This study shows that the multifunctional MgSO4//MgO/SA/Na-CMC composite hydrogel dressing developed as a surgical incision dressing has broad prospects in the prevention of incision infection, postoperative edema and analgesia.